2019
DOI: 10.1007/s12207-019-09348-8
|View full text |Cite
|
Sign up to set email alerts
|

Expert Witnesses, Dissociative Amnesia, and Extraordinary Remembering: Response to Brand et al.

Abstract: Brand et al.'s (2018) response-as well as previous works by some of the authors-reveal a recurrent and concerning picture of using lengthy, but flawed, arguments to promote the concept of dissociative amnesia. Our focus here is not so much on the weak-to-moderate correlation between measures of trauma and dissociation-we concentrate more on the weak evidence for dissociative amnesia. If triers of fact accept there is a correlation between trauma and feeling depersonalized or experiencing memory errors, we fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…The possibility of head injury causing memory impairment is particularly relevant here, especially because Harrison et al found that a history of head injury was common in the “psychogenic” cases. In addition, Harrison et al did not establish whether psychological shock or trauma caused the reported memory problems or that any recalled memories really were inaccessible for a period of time (see also Patihis, Otgaar, & Merckelbach, 2019).…”
Section: Dissociative Amnesia = Repressed Memories?mentioning
confidence: 99%
“…The possibility of head injury causing memory impairment is particularly relevant here, especially because Harrison et al found that a history of head injury was common in the “psychogenic” cases. In addition, Harrison et al did not establish whether psychological shock or trauma caused the reported memory problems or that any recalled memories really were inaccessible for a period of time (see also Patihis, Otgaar, & Merckelbach, 2019).…”
Section: Dissociative Amnesia = Repressed Memories?mentioning
confidence: 99%
“…The controversy surrounding dissociative amnesia within forensic contexts has reopened an interesting discussion (Brand et al, 2018;Brand, Schielke, Brams, & DiComo, 2017;Merckelbach, & Patihis, 2018;Patihis, Ho, Loftus, & Herrera, 2018;Patihis, Otgaar, & Merckelbach, 2019), under the denomination of memory wars (Loftus, 2004), that had been closed for some time (Freyd, Klest, & DePrince, 2010;Lindblom & Gray, 2010;Loftus, 1993;Loftus & Ketcham, 1996;Memon & Young, 1997).…”
Section: Palabras Clave: Amnesia Disociativa Memoria Traumática Guerrmentioning
confidence: 99%
“…This discussion is relevant in forensic contexts, where the acceptance of the phenomenon of repressed and later recovered memories can lead to judicial errors as, in reality, they were false memories caused by bad practices when trying to get victims to "remember" facts that had not taken place (Loftus, 2004). However, it should not be limited to whether the courts accept these theories or not (Patihis et al, 2019), as this area should be very clear. The theory about repressed memories or dissociative amnesias does not meet the criteria established in Daubert vs. Merrell Dow Pharmaceuticals, Inc. (1993); therefore, it should not be taken into consideration by the courts, because of the noise and misinformation generated among professionals due to the lack of agreements on the scientific evidence.…”
Section: Palabras Clave: Amnesia Disociativa Memoria Traumática Guerrmentioning
confidence: 99%
See 1 more Smart Citation
“…An empirical study specifically using verified childhood sexual abuse also contradicts it (Alexander 2005). Dissociative amnesia/DID sceptics agree that trauma may cause depersonalisation and memory errors but contend that there is no evidence for dissociative amnesia – even though it is now embedded in the pantheon of diagnoses in DSM-5 (Patihis 2019). They observe that dissociative amnesia requires a traumatic event to be: (a) accurately encoded and stored, (b) blocked from awareness – owing to the traumatic event – and (c) accurately retrieved in pristine form.…”
Section: A Flawed Memory Mechanism Treatment Model and The Potentialmentioning
confidence: 99%